Hazardous Alcohol Drinking and Cross-National Homicide Rates: The Role of Demographic, Political, and Cultural Context. (April 2018) - Weiss, Douglas B.; Testa, Alexander; Rennó Santos, Mateus
Cross-national research on the relationship between alcohol consumption and homicide focuses on (a) the amount of alcohol consumed rather than the manner of consumption and (b) the direct relationship between alcohol consumption and homicide rates. The current study addresses these limitations by considering consumption patterns rather than consumption levels and exploring whether the alcohol–homicide relationship is moderated by features of the social structure including youth population size, quality of governance, and the prevalence of drinking. Using a broad sample of 85 countries, we find no relationship between consumption levels and homicide rates. In contrast, hazardous consumption patterns were positively associated with homicide rates. Study results also suggest that the prevalence of drinking and the quality of governance moderate this relationship.